Statistical Quality Estimation for General Crowdsourcing Tasks - Baba, Yukino; Kashima, Hisashi (Proceedings of the AAAI Conference on Human Computation and Crowdsourcing, 2013)
One of the biggest challenges for requesters and platform providers of crowdsourcing is quality control,which is to expect high-quality results from crowd workers.We propose an unsupervised statistical quality estimation method for general crowdsourcing tasks with unstructured response formats such as article writing, program coding, and logo designing, which occupy the majority on most crowdsourcing marketplaces.